EosFit7‐GUI: a new graphical user interface for equation of state calculations, analyses and teaching. Issue 4 (20th June 2016) - Gonzalez-Platas, Javier; Alvaro, Matteo; Nestola, Fabrizio; Angel, Ross
Abstract : EosFit7‐GUI is a new full graphical user interface for analysing and fitting equations of state. Abstract : EosFit7‐GUI is a full graphical user interface designed to simplify the analysis of thermal expansion and equations of state (EoSs). The software allows users to easily perform least‐squares fitting of EoS parameters to diffraction data collected as a function of varying pressure, temperature or both. It has been especially designed to allow rapid graphical evaluation of both parametric data and the EoS fitted to the data, making it useful both for data analysis and for teaching.